Proteomic insight into phenolic adaptation of a moderately halophilic Halomonas sp. strain AAD12 - SARIYAR AKBULUT, BERNA; KAZAN, DİLEK (My University, 2011)
A gram-negative, moderately halophilic bacterium was isolated from Çamaltı Saltern area, located in the Aegean Region of Turkey. Analysis of its 16S rRNA gene sequence and physiological characteristics showed that this strain belonged to the genus Halomonas ; hence, it was designated as Halomonas sp. strain AAD12. The isolate tolerated up to 800 mg⋅L(-1) phenol; however, at elevated concentrations, phenol severely retarded cell growth. The increase in lag phase with increasing phenol concentrations indicated that the microorganism was undergoing serious adaptative changes. To understand the physiological responses of Halomonas sp. strain AAD12 to phenol, a 2-dimensional electrophoresis approach combined with mass spectrometric analysis was used. This approach showed that the expression of 14 protein spots were altered as phenol concentration increased from 200 to 800 mg⋅L(-1). Among the identified proteins were those involved in protein biosynthesis, energy, transport, and stress metabolism. So far, this is the first study on phenolic adaptation of a gram-negative, moderately halophilic bacteria using proteomic tools. The results provided new insights for understanding the general mechanism used by moderately halophilic bacteria to tolerate phenol and suggested the potential for using these microorganisms in bioremediation.
Keywords: Turkey; DNA, Bacterial; Molecular Sequence Data; RNA, Ribosomal, 16S; Halomonas; Adaptation, Physiological; Proteomics; Gene Expression Regulation, Bacterial; Phenols; Phylogeny; Water Pollutants, Chemical